Diseño de criterios de asignación para monitores de signos vitales en los servicios de hospitalización y urgencias del hospital universitario Mayor- Méderi - Cruz Quintero, Lady Natalia; Rivera Garay, Tatiana María (Escuela Colombiana de Ingeniería Julio Garavito, 2019)
The development of this work focused on creating criteria for the assignment of monitoring teams, through the verification, evaluation and comparison of the capacity of vital signs monitors in the hospitalization and emergency services of the Hospital Universitario Mayor- Méderi.
Keywords: Equipos Biomedica; Servicios Hospitalarios - Bogotá - Hospital Universitario Mayor- Méderi.; Equipos Biomedica -Monitores de Signos Vitales; Biomedical Equipment; Hospital Services - Bogotá - Hospital Universitario Mayor- Méderi.; Biomedical Equipment - Vital Signs Monitors